Malaysian Social Media Users and Empowerment through Social Surveillance - Jgin Jit, Yvonne Hoh; Firdaus, Amira Sariyati Binti (Universitas Semarang, 2022)
Introduction: Surveillance is traditionally associated with negative authoritative monitoring to control society and often viewed as invasion of state authority that disregarded citizens’ right to privacy. However, ongoing technological advancements in networked, mobile and digital technologies facilitate social transformations in surveillance. Users of digital technology can also engage in surveillance. This research explored Malaysian social media users’ awareness and perception of social surveillance and investigated the manner of which social surveillance was utilised. Methods: Drawing upon a series of in-depth interviews conducted via Facebook messenger with a selected group of Malaysian social media users, this paper explored how Malaysians understand social media as a tool of surveillance and empowerment. Malaysians, being some of the most active users on social media platforms in the world were selected for this study. Findings: Findings suggested that surveillance did not merely subject individuals to scrutiny but also offered opportunities for empowerment because of that scrutiny. Empowerment through social surveillance brought benefits to individual users and also encourages an expansion of surveillance activities. However, most do not perceive such conduct as surveillance because the interviewees viewed institutional surveillance as actual surveillance while social surveillance as a concept was foreign to them. Originality: Surveillance studies is still an emerging field in Southeast Asia and is rarely taught as an independent subject in Malaysia. This perspective of this research considered the use of surveillance as a tool for empowerment and this is not an area that is studied much in this part of the world.